Thunder Box - Hammonds, Heather; Edited by Heron, Carmel; Illustrated by Freeman, Rupert (Melbourne Nelson, 2000)
When Rob and Sean visit Grandpa Bill's farm, they discover an unusual outdoor toilet.
Keywords: Outhouses -- Real estate development